Nitric oxide formation in the metabolism of nitrates in the oral cavity - Ye. H. Romanenko; L. V. Hryhorenko; M. P. Komskyi; P. L. Sribnyk; O. O. Sinkovska (Zaporožskij Medicinskij Žurnal)
Nowadays, nitric oxide is recognized as a regulator of important vascular and metabolic functions. Nitric oxide is formed in the endothelium by converting essential amino acid L-arginine to L-citrulline with the participation of constitutional endothelial nitric oxide synthase. In addition to endogenous pathway of formation, dietary nitrate contributes to the nitric oxide generation through the successive stages (NO3-NO2-NO) mediated by salivary glands and bacteria of the oral cavity.